Spirometry and volumetric capnography in lung function assessment of obese and normal-weight individuals without asthma - Mariana S. Ferreira; Roberto T. Mendes; Fernando A.L. Marson; Mariana P. Zambon; Maria A.R.G.M. Antonio; Ilma A. Paschoal; Adyléia A.D.C. Toro; Silvana D. Severino; Maria A.G.O. Ribeiro; José D. Ribeiro
Abstract Objective: To analyze and compare lung function of obese and healthy, normal-weight children and adolescents, without asthma, through spirometry and volumetric capnography. Methods: Cross-sectional study including 77 subjects (38 obese) aged 5-17 years. All subjects underwent spirometry and volumetric capnography. The evaluations were repeated in obese subjects after the use of a bronchodilator. Results: At the spirometry assessment, obese individuals, when compared with the control group, showed lower values of forced expiratory volume in the first second by forced vital capacity (FEV1/FVC) and expiratory flows at 75% and between 25 and 75% of the FVC (p < 0.05). Volumetric capnography showed that obese individuals had a higher volume of produced carbon dioxide and alveolar tidal volume (p < 0.05). Additionally, the associations between dead space volume and tidal volume, as well as phase-3 slope normalized by tidal volume, were lower in healthy subjects (p < 0.05). These data suggest that obesity does not alter ventilation homogeneity, but flow homogeneity. After subdividing the groups by age, a greater difference in lung function was observed in obese and healthy individuals aged >11 years (p < 0.05). Conclusion: Even without the diagnosis of asthma by clinical criteria and without response to bronchodilator use, obese individuals showed lower FEV1/FVC values and forced expiratory flow, indicating the presence of an obstructive process. Volumetric capnography showed that obese individuals had higher alveolar tidal volume, with no alterations in ventilation homogeneity, suggesting flow alterations, without affecting lung volumes.